Republic of Poland : Technical Assistance Report-Progress Report on Budget System Reform-Developing a Standard Chart of Accounts and a Medium-term Budget Framework. (IMF Staff Country Reports; Country Report, 2020)
The Polish government is making good progress with implementing the ambitious Budget System Reforms (BSR) program, first approved by the Council of Ministers (CoM) in 2016. The government demonstrates a high level of commitment to these reforms and is making significant progress in implementing the recommendations of earlier FAD missions with the support of the resident advisor.